Benign fibrous histiocytoma of the external auditory canal: Case report and literature review - Rashid, Nur Hashima A; Goh, Bee See; Ghani, Fauzah A; Saim, Lokman (Bangladesh Journal of Otorhinolaryngology, 2012)
Background: The benign fibrous histiocytoma (BFH) is a mainly dermal neoplasm composed of a mixture of fibroblastic and histiocytic cells. It is usually reported as occurring on the extremity, retroperitoneum or orbit but not commonly in the other head and neck regions. Methods: A ten-year old girl presented with a right external auditory meatal mass for 6 months. Clinical examination showed a small, firm non-tender swelling on the antero-inferior part of the cartilagenous external auditory canal. An excisional biopsy was performed without complication. Results: Clinical and histopathological examinations with immunohistochemical studies were consistent with the diagnosis of BFH of the external auditory canal. There was no local recurrence to date. Conclusions: BFH is an uncommon benign neoplasm of the head and neck and none has been previously described occurring in the external auditory canal. Complete local excision is the mainstay of treatment with excellent prognosis. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10424 Bangladesh J Otorhinolaryngol 2012; 18(1): 77-80